An Analysis of Digital Learning Media Utilization in Social Studies Education from Peusangan District Junior High Schools - Salsabila Salsabila; Mauliana Wayudi; Zulfikar Zulfikar (LPPM STKIP Kusuma Negara, 2026)
Supporting the 24th-century learning process requires the utilization of digital-based learning resources. However, several issues persist in its implementation within Social Studies (IPS) instruction in junior high schools (SMP), particularly regarding the availability of resources and facilities. This study aims to examine how digital-based learning resources are utilized in Social Studies classrooms across seven public junior high schools in Peusangan District and to identify the internal and external factors influencing this utilization. This study employs a case study method with a qualitative approach. Data were collected through observations, interviews, and documentation from Social Studies teachers. The findings indicate the integration of digital media in the learning process, including educational films, interactive PowerPoint presentations, and various learning tools. The deployment of these technologies renders learning more dynamic, simplifies information delivery, and enhances student engagement. Nonetheless, infrastructural constraints, a lack of training, and disparities in teachers' digital competencies have hindered optimal implementation. The results suggest that maximizing the use of digital-based learning materials in Social Studies instruction requires strengthening school policies, improving teachers' digital skills, and enhancing infrastructure support.